FROM BIOLOGY TO THE BEDSIDE-SIRTUINS AS TARGETS FOR DISEASE MODIFICATION IN HUNTINGTON'S DISEASE: SELISISTAT PRECLINICAL DATA AND PRELIMINARY PHASE I RESULTS. (29th November 2012) - Haider, SS; Landwehrmeyer, BG; Sissumuth, SD; Frost, C; Farmer, R; Andre, R; Caricasole, A; Crauford, DI; Westerberg, G; Tabrizi., SJ
Abstract : To date no disease modifying therapy has shown efficacy in Huntington's Disease (HD). The PADDINGTON (Pharmacodynamic Approaches to Disease Modification in Huntington's Disease) Project, funded by the European Union's Seventh Framework Programme, aims to develop biomarkers to quantify disease modification. As part of this project, early phase clinical trials of selisistat (SEN0014196), an inhibitor of SirT1 (silencing information regulator T1) developed by Siena Biotech, are in progress. Sirtuins, which are deacetylating enzymes, are potential targets in aging, metabolism and neurodegeneration. Selisistat has a novel mode of action that may be pathologically relevant for Huntington's Disease. Inhibition of SirT1 in transgenic mice and Drosophila HD models lowers mutant Huntingtin protein levels and ameliorates HD phenotypes. In cellular models, modulation of Huntingtin acetylation and clearance is proposed as a potential mechanism. A first time in human study, employing a randomized, double-blind, placebo-controlled design with single dose escalation and multiple dose format, demonstrated safety and tolerability in healthy volunteers with low incidence of adverse events. A Phase 1B study in 55 HD patients, encompassing six EU sites (Germany, Poland and the UK), was carried out over 14-days at two dose levels with a randomized, double-blind, placebo-controlled, parallel group design. A Phase 2 study, involving a 12 week dosing period is underway across Europe including 7 UK sites. Here we present safety, tolerability and pharmacodynamic data from the Phase 1B study.